Local transformation processes that detonate the change of land and vegetation use in a protected natural area of the Central Mexico Region - Gómez Demetrio, William; Martínez, Daniel Villegas (Acta Universitaria, 2020)
The processes of change of land and vegetation use in Mexico are a phenomenon caused by the expansion of anthropic activities. Given this and other problems, the generation of strategies through the decree of protected natural areas seeks to protect the integrity of representative ecosystems. Nevertheless, the lack of implementation of management policies in these geographical spaces makes evident their socio-environmental deterioration. Under this preamble, the objective of this research was to identify, locate and spatially analyze the transformation processes that directly affect the changes in land and vegetation use within the administrative territory of the Otomi-Mexica Park in the State of Mexico. Through the generation of land and vegetation use coverings of the years 1993 and 2018, application of overlay methods, photointerpretation techniques and field work, it is determined that changes in land and vegetation use are generated by conversion processes, modification and fragmentation.